A significant therapeutic effect of silymarin administered alone, or in combination with chemotherapy, in experimental pulmonary tuberculosis caused by drug-sensitive or drug-resistant strains: In vitro and in vivo studies. - Edén M Rodríguez-Flores; Dulce Mata-Espinosa; Jorge Barrios-Payan; Brenda Marquina-Castillo; Mauricio Castañón-Arreola; Rogelio Hernández-Pando (PLoS ONE, 2019)
For many years, tuberculosis (TB) has been a major public health problem worldwide. Advances for treatment and eradication have been very limited. Silymarin (Sm) is a natural product with antioxidant and hepatoprotective activities that has been proposed as a complementary medicine to reduce the liver injury produced by the conventional anti-TB chemotherapy. Sm also has immunoregulatory and microbicide properties. In this study, we determined the effect of Sm on the growth control of mycobacteria. In vitro studies showed that Sm and Silibinin (the principal active compound of Sm) have microbicidal activity against drug-sensitive and multidrug-resistant (MDR) mycobacteria, induce the production of protective cytokines from infected macrophages, and improve the growth control of mycobacteria (p ≤ 0.0001). Studies in vivo using a model of progressive pulmonary TB in BALB/c mice infected with drug-sensitive or MDR mycobacteria have shown that Sm induces significant expression of Th-1 cytokines such as IFN-γ and IL-12 as well as TNFα, which produce significant therapeutic activity when administered alone and apparently have a synergistic effect with chemotherapy. These results suggest that Sm has a bactericidal effect and can contribute to the control and establishment of a TH1 protective immune response against mycobacterial infection. Thus, it seems that this flavonoid has a promising potential as adjuvant therapy in the treatment of TB.